2013
DOI: 10.1177/0023677213514043
|View full text |Cite
|
Sign up to set email alerts
|

Ethograms indicate stable well-being during prolonged training phases in rhesus monkeys used in neurophysiological research

Abstract: Awake, behaving rhesus monkeys are widely used in neurophysiological research. Neural signals are typically measured from monkeys trained with operant conditioning techniques to perform a variety of behavioral tasks in exchange for rewards. Over the past years, monkeys' psychological well-being during experimentation has become an increasingly important concern. We suggest objective criteria to explore whether training sessions during which the monkeys work under controlled water intake over many days might af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Laboratory fluid protocols, therefore, are not expected to constitute an unknown physiological challenge, as shown by the absence of detectable changes regarding kidney function, water balance, or general health in our data. Given that (1) task requirements in the laboratory are accessible for the monkey to obtain its desired amount of liquid, (2) behavior and body weight is continuously monitored to allow identification of low hydration, (3) possible deficiencies may be compensated on non-training days, and (4) handling and overall laboratory conditions prevent anxiety and stress, there is also not much reason to assume a priori an impairment in psychological well-being during periods of controlled fluid supply, in line with the behavioral scores we reported here, and the ethograms of previous studies ( Hage et al, 2014 ; Gray et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Laboratory fluid protocols, therefore, are not expected to constitute an unknown physiological challenge, as shown by the absence of detectable changes regarding kidney function, water balance, or general health in our data. Given that (1) task requirements in the laboratory are accessible for the monkey to obtain its desired amount of liquid, (2) behavior and body weight is continuously monitored to allow identification of low hydration, (3) possible deficiencies may be compensated on non-training days, and (4) handling and overall laboratory conditions prevent anxiety and stress, there is also not much reason to assume a priori an impairment in psychological well-being during periods of controlled fluid supply, in line with the behavioral scores we reported here, and the ethograms of previous studies ( Hage et al, 2014 ; Gray et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…Blood levels of urea, sodium, and creatinine, and the hematocrit, however, were the same as during free access. Ethograms derived from videotaped material did not provide indication of increased anxiety or other consistent behavioral observations to suggest a decrease in well-being during limited fluid supply, in line with another study ( Hage et al, 2014 ). Both studies concluded that fluid control has less of an impact than often proposed.…”
Section: Discussionsupporting
confidence: 85%
“…Yamada et al (2010) found that increases in macaque blood osmolality (Osm), caused by fluid control, could be quickly restored over the course of a behavioral task, and that osmolality remained mostly stable across a 5 day (d) working week. More recently, Hage et al (2014) failed to detect any changes in home cage behavior across a 12 d period of fluid control. Although both of these studies help to alleviate some concerns of fluid control protocols, it could be argued that they are too focused on one particular type of measure or are too short term to address concerns about the long-term impacts on welfare.…”
Section: Introductionmentioning
confidence: 99%
“…These require a high number of consecutively performed trials to achieve adequate data quality, statistical reliability, and sample sizes suitable for complex model testing. To achieve adequate daily performance, laboratories often use fluid rewards as motivators for correct trial performance and restrict fluid access for the animals outside of the experiment (Desimone et al, 1992; Newsome and Stein-Aviles, 1999; Toth and Gardiner, 2000; Hage et al, 2014). Despite the widespread use of fluid control protocols, and the justification for their implementation, their use has been an issue of increasing contention for >20 years (Orlans, 1991; Desimone et al, 1992; Willems, 2009; Prescott et al, 2010; Westlund, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To quantify daily activity budgets, detailed ethograms can be created [ 75 , 76 ]. In the context of pain, ethograms can be helpful to quantify the reduction in normal or species-typical behaviour and the appearance of pain-related behaviours [ 77 ]. Software systems such as Observer XT can facilitate behavioural scoring and statistical analysis; however, conducting these assessments is laborious, inter- and intra-observer reliability needs to be assessed, and assessments need to be conducted in real time to be useful.…”
Section: Pain Assessments In Research Primates—a Reviewmentioning
confidence: 99%